System Dynamics Modeling of Lighting Electricity Demand in the Urban Residential Sector of Nepal - Bajracharya, Iswor; Bhattarai, Nawraj (Journal of Development and Administrative Studies, 2016)
A significant portion of the total electricity is consumed in the residential sector of Nepal, mainly for lighting purpose. In this study, a model has been developed using the concept of system dynamics to analyze the dynamics of the changes in the urban residential lighting electricity demand up to the year 2030. A system dynamics modeling tool, Venism, has been used for this purpose. This study is useful for the utilities of companies for the power capacity expansion planning. Altogether three different scenarios have been developed. They are Reference Scenario (Ref), LED Lamp (LL) Scenario and Incandescent Lamp Remove (ILR) Scenario. The study has shown that lighting electricity consumption has already been in the decreasing trend due to the increasing use of Clear Fluorescent Lamp (CFL) and will be the minimum somewhere in the year between 2021 and 2022. Only a small portion of the total electricity will be consumed for lighting the household in the urban residential sector of Nepal in the coming decade. Therefore, government should focus the urban energy efficiency program for other uses of electricity such as cooking, water heating and water pumping etc. so that a significant amount of electricity can be saved in the urban households of Nepal. This study has also shown that there is no difference between the use of CFL and LED lamps from the energy saving point of view. Therefore, like the case of incandescent lamp and CFL, there is no need to encourage the people to buy LED lamp instead of CFL. The Journal of Development and Administrative Studies (JODAS) Vol. 23(1-2), pp. 33-54